The werewolf of Fever Swamp - Stine, R. L. (New York : Scholastic, 2009)
Grady begins to suspect his new pet might be a werewolf when a series of strange incidents occur in Fever Swamp right after the dog's arrival.
"Now with bonus features!"--Cover.
4.1
5-8
Keywords: Werewolves -- Juvenile fiction; Horror stories; Werewolves -- Fiction; Horror fiction; Werewolves -- Fiction; Horror fiction